Edge-pancyclicity of pancake graph. Issue 3 (2nd July 2020) - Hung, Chun-Nan; Abdallah, Mohamad; Weng, Jui-I; Kung, Tzu-Liang
ABSTRACT: Pancylicity was introduced by Bondy in 1971. A graph G with vertex set V ( G ) and edge set E ( G ) is pancyclic if it contains cycles of lengths l, for 3 ≤ l ≤ | V ( G ) | . This concept has been extended to edge-pancyclicity . If every edge of G is in a cycle of every length, G is edge-pancyclic . If every edge lies on cycles of all lengths ranging from k to | V ( G ) |, G is k-edge-pancyclic . In this paper, we prove that the n -dimensional pancake graph is 7-edge-pancyclic.